2000
DOI: 10.1046/j.1440-1681.2000.03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol‐Induced Hypertrophy May Result In Distinct Left Ventricular Changes

Abstract: 1. The aim of the present study was to analyse the possible lack of uniformity in isoproterenol (ISO)-induced myocardial hypertrophy. 2. Data obtained for isovolumic hearts isolated from 20 rats treated with ISO (0.3 mg/kg over 8 days) were divided into two groups (H1, n = 10; H2, n = 10) according to the volume (mean+/-SD) needed to change left ventricle diastolic pressure from 0 to 40 mmHg (H1, 184+/-30 microL; H2, 108+/-14 microL). Eight control rats (C; 165+/-37 microL) were used for comparison. 3. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
6
8
0
1
Order By: Relevance
“…Non-trained ISO-treated rats (Group I) had significantly smaller LV chamber diameter and increased free wall thickness (Table 1) characterizing the occurrence of LV concentric hypertrophy, which corroborates previous findings in our lab [20]. The ISO-treated rats showed significantly increased nuclear volume in LV (Table 1), multiple foci of subendocardial necrosis, subendocardial fibrosis, and increased myocardial collagen.…”
Section: Optical Microscopysupporting
confidence: 89%
“…Non-trained ISO-treated rats (Group I) had significantly smaller LV chamber diameter and increased free wall thickness (Table 1) characterizing the occurrence of LV concentric hypertrophy, which corroborates previous findings in our lab [20]. The ISO-treated rats showed significantly increased nuclear volume in LV (Table 1), multiple foci of subendocardial necrosis, subendocardial fibrosis, and increased myocardial collagen.…”
Section: Optical Microscopysupporting
confidence: 89%
“…Similar findings of little or no change in cardiac function have been reported in rats treated with low doses (0.2-0.4 mg/kg body mass) of isoproterenol (24,433), although it has been suggested that in rats, the changes to the heart during isoproterenolinduced cardiac hypertrophy are not homogeneous and that myocardial mass, myocardial relaxation, left ventricular stiffness, and systolic function can differ between subgroups of animals (318).…”
Section: A Effects Of ␤-Agonists On Cardiac Muscle Structure and Funsupporting
confidence: 72%
“…The structural changes in rat myocardium following chronic ISO administration are not uniform, with myocardial necrosis and reparative fibrosis prevailing over stimulation of the myocyte growth in some animals [118]. Importantly, the accumulation of collagen fibers in LV subendocardium tends to extend outwards from intermuscular spaces and encircle the ventricular fibers [99,100,118,119].…”
Section: Morphological Changes In Heart Tissuementioning
confidence: 99%
“…Importantly, the accumulation of collagen fibers in LV subendocardium tends to extend outwards from intermuscular spaces and encircle the ventricular fibers [99,100,118,119]. This effect contributes to increased myocardial stiffness and impaired diastolic relaxation.…”
Section: Morphological Changes In Heart Tissuementioning
confidence: 99%